Strengthening school literacy programs with support from library collection development - Ghina Afiifah Safiinatunnajah; Dina Siti Logayah (Universitas Pendidikan Indonesia, 2023)
Literacy is a skill that everyone must own. This literacy skill includes processing, understanding, and interpreting information about matters in specific fields. The information was obtained as support and survival. The urgency of cultivating literacy is becoming an increasingly important topic to be intensified at this time. Various ways are done so the community can fully master that literacy. One of them is by empowering the school library. Empowerment of the school library in this activity focuses on collection development. The development of school library collections is an activity schools must carry out to support student learning facilities. However, several schools still need to implement library collection development. One of them is the UPI Literacy Thematic KKN activity, namely at the Tahfidzul Qur'an Al-Ishlah Putri Islamic Boarding School, which is located in Bogor Regency. Based on these problems, the author seeks to design a community service program in the Tahfidzul Qur'an Al-Ishlah Putri Islamic Boarding School library to support the school's literacy program. The service method implemented is strengthening the school literacy program with support for developing library collections. The results of this program are a concern and the starting gate for the sustainability of literacy activities at the Tahfidzul Qur'an Al-Ishlah Putri Islamic Boarding School.